Implementación virtual de un proceso de clasificación de cajas de diferentes tamaños mediante tia portal y factory i/o en el contexto de la industria 4.0 (2021)
The present work named virtual implementation of a process of classification, and packaging of boxes of various sizes through TIA portal and Factory I / O on the context of industry 4.0. Seek to encourage businesses on their recent technologies called the fourth industrial revolution or industry 4.0. This technology seeks to unify the diverse traditional hierarchical levels of the industries, opening a space for the performance of smart grids throughout the value chain, preventing the loss of data to make more agile and effective the decision-making to anticipate future problems. This project proposes to clear up the following problem: from a virtual process of sorting and packing boxes of three different sizes how the data from PLC can be captured through the different connected devices and directed it to the cloud for its visualization? The solution to this problem is conducted by managing industry 4.0 technologies where tools such as simulation, communication and cloud computing will be employed. For developing this process, three phases will be implemented: first: through simulators, the sensors and actuators corresponding to the PLC controller will be identified. Second: the search of the simulator for the PLC controller will be executed. At that point, the collection of the data obtained from the controller will be uploaded through the cloud computing services for their corresponding visualization. Third: Analyze the performance of the PLC by quantifying the times variable on the line of sorting and packaging process of boxes of various sizes.